Poly(methacrylates) with Pendant Benzoquinone Units – Monomer Synthesis, Polymerization, and Electrochemical Behavior: Potential New Polymer Systems for Organic Batteries. Issue 12 (21st May 2014) - Häupler, Bernhard; Ignaszak, Anna; Janoschka, Tobias; Jähnert, Thomas; Hager, Martin D.; Schubert, Ulrich S.
<x xml:space="preserve">Abstract</x> Redox‐active polymers became the focus of attention in the field of organic electronics during the last decade. Quinoide systems are intensively studied in this field. Although benzoquinones are generally known as radical scavengers, certain monomers can be polymerized by radical polymerization techniques. For this purpose, methacrylate functionalities are attached to the redox‐active quinone moiety. A free‐radical polymerization technique is applied utilizing AIBN as initiator. The molar mass can be adjusted by the choice of an appropriate solvent system. Electrochemical investigations of these new monomers and polymers, in particular cyclic voltammetry, are performed in aqueous and non‐aqueous electrolytes in the dissolved and solid states, showing the potential usefulness of the system for applications in organic radical batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>